Dietary agent, benzyl isothiocyanate inhibits signal transducer and activator of transcription 3 phosphorylation and collaborates with sulforaphane in the growth suppression of PANC-1 cancer cells - Hutzen, Brian (BioMed Central, 2009)
The Signal Transducer and Activator of Transcription (STAT) proteins comprise a family of latent transcription factors with diverse functions. STAT3 has well established roles in cell proliferation, growth and survival, and its persistent activation has been detected with high frequency in many human cancers. As constitutive activation of STAT3 appears to be vital for the continued survival of these cancerous cells, it has emerged as an attractive target for chemotherapeutics. We examined whether the inhibitory activities of bioactive compounds from cruciferous vegetables, such as Benzyl isothiocyanate (BITC) and sulforaphane, extended to STAT3 activation in PANC-1 human pancreatic cancer cells. BITC and sulforaphane were both capable of inhibiting cell viability and inducing apoptosis in PANC-1. Sulforaphane had minimal effect on the direct inhibition of STAT3 tyrosine phosphorylation, however, suggesting its inhibitory activities are most likely STAT3-independent. Conversely, BITC was shown to inhibit the tyrosine phosphorylation of STAT3, but not the phosphorylation of ERK1/2, MAPK and p70S6 kinase. These results suggest that STAT3 may be one of the targets of BITC-mediated inhibition of cell viability in PANC-1 cancer cells. In addition, we show that BITC can prevent the induction of STAT3 activation by Interleukin-6 in MDA-MB-453 breast cancer cells. Furthermore, combinations of BITC and sulforaphane inhibited cell viability and STAT3 phosphorylation more dramatically than either agent alone. These findings suggest that the combination of the dietary agents BITC and sulforaphane has potent inhibitory activity in pancreatic cancer cells and that they may have translational potential as chemopreventative or therapeutic agents.